PROPOSED BRAND ACTIVATION STRATEGY FOR A NEW WOMENâS FASHION BUSINESS (Case Study : Aubre and Liesse) - Rustine, Mira
Since 2010 many local fashion brands have been established in Indonesia. The great demand and opportunity of fashion products and businesses create a high-level competition that the fashion industry has become a “red ocean”. In 2016 there were 1,230,988 fashion companies (BEKRAF, 2017) and the main competition is not with the foreign brands but with fellow local brands.